Genome Analysis and Description of Three Novel Diazotrophs Geomonas Species Isolated From Paddy Soils - Liu, Guo-Hong; Yang, Shang; Tang, Rong; Xie, Cheng-Jie; Zhou, Shun-Gui (Frontiers in Microbiology, 2022)
Five strictly anaerobic strains, designated RG2T, RG3, RG10T, RF4T and RG29, were isolated from paddy soils in China. Strains RG2T, RF4T, RG10T, RG3 and RG29 grew at temperatures ranging 5-42 °C and pH ranging 5.5-8.5. Strains RG2T, RF4T, RG3 and RG29 could tolerate NaCl up to 0-0.7 % (w/v) while strain RG10T could tolerate NaCl up to 0-0.8 % (w/v). The isolated strains showed the highest 16S rRNA gene sequence similarities to the type strains of Geomonas terrae Red111T and Geomonas paludis Red736T. In phylogenetic (based on 16S rRNA gene sequence) and phylogenomic tree, strains clustered with the members of the genus Geomonas. Menaquinone-8 was the predominant quinone present in all strains. The major fatty acid profiles of all strains were C15:1 ω6c, C16:0, iso-C15:0, and Summed Feature 3. The digital DNA-DNA hybridization (dDDH) and average nucleotide identity (ANI) values between the isolated strains and the closely related Geomonas species were lower than the cut-off value (ANI 95–96 % and dDDH 70 %) for prokaryotic species delineation. Based on physiological, biochemical and chemotaxonomic properties, strains RG2T, RG10T and RF4T could easily be differentiated with the members of the genus Geomonas. Additionally, all the isolated strains possessed nifHDK clusters and catalytic compartments of nitrogenase. Based on the above results, the isolated five strains represent three novel species of the genus Geomonas, for which the names Geomonas oryzisoli sp. nov., Geomonas subterranea sp. nov., and Geomonas nitrogeniifigens sp. nov. are proposed. The type strains are RG10T (= GDMCC1.2537T = KCTC 26318T), RG2T (= GDMCC1.2536T = KCTC 25317T) and RF4T (=GDMCC 1.2547T = KCTC 25316T).